Village Japan : Everyday Life in a Rural Japanese Community. - Ritchie, Malcolm (Tuttle Pub., 2011)
In this elegiac account that is part travelogue, part memoir, British poet and writer Malcolm Ritchie recounts his and his wife's unforgettable three-year-sojourn in Sora, a remote farming and fishing village on the Japan Sea coast. Ritchie weaves together anecdotes, conversations, lyrical verses, and unforgettable character studies to vividly and hauntingly evoke the rhythms of life in a traditional rural Japanese community. Underlying this portrait is the author's growing awareness that the aged inhabitants of Sora and the surrounding villages are the custodians of a fragile, barely survivin.